Synthesis Carboxyl Methyl Cellulose (CMC) from Rice Straw (Oryza Sativa L.) Waste - Masrullita, Masrullita; Nurlaila, Rizka; Zulmiardi, Zulmiardi; Safriwardy, Ferri; Auliani, Auliani; Meriatna, Meriatna (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Rice straw is one of material containing cellulose to produce Carboxymethyl Cellulose (CMC). CMC is a non toxic polysaccharide that produces from cellulose that widely used in the pharmaceutical, food, textile, detergent, and cosmetic products industries. There are two stages usually use to produce CMC which are mercerization and esterification processes. Rice straw waste is one of the materials to produce CMC, it has a cellulose content of 37.7%, hemi-cellulose 21.99%, and lignin 16.62 %.Â BPS Aceh shown that the total rice harvested area was 310.01 hectares, with a total production of 1.71 million tons, and rice produced at 982.57 thousand ton. This study aims to reduce waste and environmental pollution caused by rice straw and collects information of rice straw as a basic material to produce of carboxymethyl cellulose and to increase the economic value of rice straw.Â The effects of various wieght parameters sodium monochloroacetate on chemical properties of CMC that produce from rice straw were investigated in this research. Rice straw was collected from a rice field in Nisam, North Aceh. The research conducted by synthesizing 5 grams rice straw for 5.5 hours using NaOH and Sodium Monochloroacetate solutions. With variations weight of sodium monochloroacetate are 5,6,7,8 and 9 grams. The characterization of CMC was carried out by Fourier Transform Infrared (FTIR), CMC yield, DS, Viscosity, water content, pH. The result shows that addition of sodium monochloroacetate was significant factors influence the chemical properties on CMC. The CMC that produced in this study achieved to National Indonesia Standard (SNI).